Bioinformatics in Action : A Comprehensive Review of Bioinformatics Applications in Varied Disciplines - Dewi, Adhe; Setyo Adhi, Canggih Gelar (AI Society & STMIK Indonesia, 2024)
Studies have been carried out related to the application of bioinformatics which includes genomics, proteomics and metabolomics in everyday life, such as in the fields of health, agriculture, environment, renewable energy and food. Evaluation of the quality of the papers used is based on papers available in each journal on platforms such as Scopus, Google Scholar, as well as articles published by Elsivier, Springer Nature, etc. The stages carried out in this research include journal data collection, journal renewal, journal grouping, and journal comparison. Based on this application, it has been proven that bioinformatics has achieved success in understanding various biological aspects. Thus, it is hoped that this research can provide deeper insight regarding the use of bioinformatics in various other fields.